2019
DOI: 10.3389/fmars.2019.00398
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Ranging Temporal Variation in Transoceanic Movement and Population Mixing of Bluefin Tuna in the North Atlantic Ocean

Abstract: Uncertainty regarding the movement and population exchange of Atlantic bluefin tuna (Thunnus thynnus) from the two primary spawning areas (Gulf of Mexico, Mediterranean Sea) is increasingly implicated as a major impediment for the conservation of this species. Here, two mixture methods were applied to natural chemical markers (δ 18 O and δ 13 C) in otoliths (ear stones) to comprehensively investigate the nature and degree of transoceanic movement and mixing of eastern and western populations in several areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 57 publications
1
50
0
1
Order By: Relevance
“…Cuttlebone δ 13 C and δ 18 O were quantified for core and edge material to characterize geochemical signatures associated with early ( juvenile) and recent (sub-adult/adult) life-history periods, respectively. Regional shifts in cuttlebone δ 13 C and δ 18 O values were detected across the 12 sites investigated. Individuals collected from sites in the NEAO displayed more enriched δ 13 C and δ 18 O values relative to sites in the Mediterranean Sea, with the latter also showing salient differences in both markers among western, central and eastern collection areas.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Cuttlebone δ 13 C and δ 18 O were quantified for core and edge material to characterize geochemical signatures associated with early ( juvenile) and recent (sub-adult/adult) life-history periods, respectively. Regional shifts in cuttlebone δ 13 C and δ 18 O values were detected across the 12 sites investigated. Individuals collected from sites in the NEAO displayed more enriched δ 13 C and δ 18 O values relative to sites in the Mediterranean Sea, with the latter also showing salient differences in both markers among western, central and eastern collection areas.…”
mentioning
confidence: 95%
“…Regional shifts in cuttlebone δ 13 C and δ 18 O values were detected across the 12 sites investigated. Individuals collected from sites in the NEAO displayed more enriched δ 13 C and δ 18 O values relative to sites in the Mediterranean Sea, with the latter also showing salient differences in both markers among western, central and eastern collection areas. Classification success based on cuttlebone δ 13 C and δ 18 O values to four geographical regions (NEAO, western, central and eastern Mediterranean Sea) was relatively high, suggesting that environmental conditions in each region were distinct and produced area-specific geochemical signatures on the cuttlebones of S. officinalis.…”
mentioning
confidence: 95%
“…Chemical analysis of otoliths has been conducted on over 41 fish species from the Mediterranean, and the most studied species are from the family Sparidae (Table 1). Published studies include data for the entire otolith (e.g., Iacumin et al, 1992;Gillanders et al, 2001;Marini et al, 2006;Arechavala-Lopez et al, 2016), data for a specific area of the otolith (e.g., Tanner et al, 2012;Mirasole et al, 2017;Rooker et al, 2019), and time series data (e.g., Correia et al, 2012;Mercier et al, 2012;Bouchoucha et al, 2018). In most reports, only a single species was analyzed, while Papadopoulou and Moraitopoulou-Kassimati (1977), Iacumin et al (1992), Marini et al (2006), Swan et al (2006), Khemiri et al (2014), Arechavala-Lopez et al (2016), Mirasole et al (2017), Bouchoucha et al (2018), and Demirci et al (2018) presented data for 2 to 24 different species.…”
Section: Overview Of Previous Sclerochronology Related Research In Thmentioning
confidence: 99%
“…The majority of research on otolith chemical composition has been conducted on commercially important species. Atlantic Bluefin tuna (Thunnus thynnus) was the target of several studies on the element (Secor and Zdanowicz, 1998;Rooker et al, 2003) and isotope composition (Secor et al, 2002;Rooker et al, ,b, 2014Rooker et al, , 2019, aiming to reconstruct movement and population exchange. Fraile et al (2016) observed the depletion in δ 13 C in T. thynnus otoliths over time, associating this with the oceanic uptake of anthropogenically derived CO 2 from the Mediterranean Sea over the past two decades.…”
Section: Family Species Referencesmentioning
confidence: 99%
See 1 more Smart Citation